Tailoring ultraviolet-green to white light via energy transfer from Tb3+ - Eu3+ codoped glasses for white light-emitting diodes. (October 2020) - Vijayalakshmi, L.; Kumar, K. Naveen; Hwang, Pyung
Abstract: The photoluminescence properties of lithium borate glasses doped with Tb 3+ and Eu 3+ ions individually and together were explored. The combination of bright green and orange-red emissions from the optimized glasses can generate white light under ultraviolet excitation. The red emission of Eu 3+ ions was remarkably improved by external doping with Tb 3+ ions by means of energy transmission from Tb 3+ to Eu 3+ . The correlated color temperature and chromaticity coordinates were significantly changed from warm reddish to cool white region in Eu 3+ and (Tb 3+ +Eu 3+ ):lithium borate glassy matrices, respectively, which were found to be a good candidates for white light emitting device applications. Graphical abstract: Image, graphical abstract